2014
DOI: 10.1542/neo.15-12-e514
|View full text |Cite
|
Sign up to set email alerts
|

Educational Perspectives: Telesimulation in Neonatal Resuscitation

Abstract: Health care professionals practicing in rural and critical access hospitals face a great diversity of clinical problems but often only have access to limited support. Geographic boundaries can construct barriers to continuing professional development. In addition, neonatal emergencies may arise infrequently at any given location. Thus, to improve neonatal resuscitation outcomes, particularly at remote and rural sites, it is likely necessary to increase the frequency with which physicians and staff are provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…They also reported that simulation and distance education allows isolated medical personnel the opportunity to practice skills unconstrained by time or distance 19. Telesimulation has also received favorable reviews in fields such as pediatric critical care and neonatal resuscitation 2022…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that simulation and distance education allows isolated medical personnel the opportunity to practice skills unconstrained by time or distance 19. Telesimulation has also received favorable reviews in fields such as pediatric critical care and neonatal resuscitation 2022…”
Section: Discussionmentioning
confidence: 99%
“…Telesimulation has been used to teach a variety of technical emergency medicine skills, such as surgical knots [ 17 ] and intraosseous needles [ 18 ]. It has also been used to teach resuscitations that require team communication skills [ 19 - 20 ]. However, little has been reported on its utility for teaching both (a) a high-stakes low-frequency procedure and (b) communication skills between rural health practitioners and distantly-placed urban consultants.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have been performed in regions of the world with limited resources that do not have access to costly simulation laboratories, supplies, or trained instructors. Telesimulation has also been used for instruction in critical care fields such as emergency medicine, pediatric anesthesia, and neonatal resuscitation, with some studies utilizing high‐fidelity simulators without the duplication of resources at student locations …”
Section: Demonstrated Applications Of Telesimulationmentioning
confidence: 99%